Phase‐Separable Polyisobutylene Palladium‐PEPPSI Precatalysts: Synthesis and Application in Buchwald–Hartwig Amination. Issue 15 (19th June 2017) - Balogh, Janos; Hlil, Antsar Rih; El‐Zoghbi, Ibrahim; Rafique, Muhammad Ghufran; Chouikhi, Dalila; Al‐Hashimi, Mohammed; Bazzi, Hassan S.
Abstract : Polyisobutylene‐supported palladium–PEPPSI is used for Buchwald–Hartwig amination of aryl chlorides. Abstract : This paper reports the efficient synthesis of the first class of polyisobutylene(PIB)‐supported palladium‐PEPPSI precatalyst (PEPPSI = pyridine‐enhanced precatalyst preparation, stabilization, and initiation). The new complexes are employed in Buchwald–Hartwig amination of aryl chlorides and are found to be reasonably active in the titled cross‐coupling reaction. The supported catalysts are tested in polar (1, 4‐dioxane and 1, 2‐dimethoxyethane) as well as in aliphatic reaction media (toluene and n ‐heptane) and display superior activity in the highly lipophilic solvent ( n ‐heptane). The catalytic efficacy of PIB‐Pd‐PEPPSI precatalyst is measured to be comparable to its nonsupported analog. Pd‐leaching is determined by inductively coupled plasma mass spectrometry (ICP‐MS) after a simple liquid/liquid extraction and is found to be 2 ppb in the product phase, translating into a recovery of ≈99.8% of the palladium.